2003
DOI: 10.1007/s00401-003-0734-x
|View full text |Cite
|
Sign up to set email alerts
|

The L266V tau mutation is associated with frontotemporal dementia and Pick-like 3R and 4R tauopathy

Abstract: We report a case of rapidly progressive frontotemporal dementia presenting at age 33 years. At autopsy there was severe atrophy of the frontal and temporal lobes. Tau-positive Pick bodies, which ultrastructurally were composed of straight filaments, were present, accompanied by severe neuronal loss and gliosis. RD3, a tau antibody specific for the three-repeat (3R) isoforms, labeled the Pick bodies. ET3, a four-repeat (4R) isoform-specific tau antibody, did not label Pick bodies, but highlighted rare astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 50 publications
5
73
3
Order By: Relevance
“…We selected cases with a clinical diagnosis of bvFTD and a primary neuropathological diagnosis of PiD (n=11) or FTLD-TDPC (n=10) and normal controls with a neuropathological diagnosis of unremarkable adult brain (n=5) ( Table 1). Genetic screening for C9orf72, GRN, and MAPT mutations, as reported elsewhere (Irwin et al 2013a;Irwin et al 2013b), revealed that one PiD case had a pathogenic mutation in MAPT gene (p.Leu266Val) that was associated with PBs composed of 3R isoforms of tau with the same morphology as in sporadic disease (Hogg et al 2003). Further, one additional case harbored a C9orf72 repeat expansion (i.e.…”
Section: Patientsmentioning
confidence: 63%
“…We selected cases with a clinical diagnosis of bvFTD and a primary neuropathological diagnosis of PiD (n=11) or FTLD-TDPC (n=10) and normal controls with a neuropathological diagnosis of unremarkable adult brain (n=5) ( Table 1). Genetic screening for C9orf72, GRN, and MAPT mutations, as reported elsewhere (Irwin et al 2013a;Irwin et al 2013b), revealed that one PiD case had a pathogenic mutation in MAPT gene (p.Leu266Val) that was associated with PBs composed of 3R isoforms of tau with the same morphology as in sporadic disease (Hogg et al 2003). Further, one additional case harbored a C9orf72 repeat expansion (i.e.…”
Section: Patientsmentioning
confidence: 63%
“…We had previously developed two monoclonal antibodies; RD3 and RD4, specific for 3R-and 4R-tau isoforms, respectively and these antibodies have now been extensively utilised in several neuropathological studies (de Silva et al, 2003Hogg et al, 2003;Kitamura et al, 2005;Togo et al, 2002). In this paper, we describe the development of the first sandwich ELISAs to quantify 3R-and 4R-tau, using these antibodies.…”
Section: Introductionmentioning
confidence: 97%
“…The importance of tau in human OLGs has been largely obtained from studying CNS degenerative diseases [37,38,39,40,41,42,43]. Immunohistochemical staining of OLGs in selected tauopathies reveals (in OLGs) ~14 nm diameter tubules in perikarya (coiled bodies) and outer loop processes of myelin sheath (argyrophilic threads) [37,40].…”
Section: Mechanisms Of Tau Regulationmentioning
confidence: 99%